2007
DOI: 10.1007/s10620-006-9661-8
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranylacetone Induces Cyclooxygenase-2 Expression in Cultured Rat Gastric Epithelial Cells Through NF-κB

Abstract: Geranylgeranylacetone (GGA) effectively protects the gastric mucosa against noxious agents. The precise mechanisms underlying the gastroprotective actions of GGA are not known. To elucidate the precise mechanism of GGA, the effect of GGA treatment on COX-2 expression in rat gastric epithelial (RGM1) cells was investigated. We used a prostaglandin E2 (PGE2) enzyme-linked immunoassay kit and Western blot analysis to measure PGE2 production and COX-2 induction by GGA treatment in serum-starved RGM1 cells. Gel-shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 46 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Indeed, we previously administered a COX-2 inhibitor to mice with DSS-induced colitis and demonstrated that the presence of a COX-2 inhibitor during colitis exacerbated the colitis and did not show a preventive effect against colitis-induced tumorigenesis (13). Nishida et al evaluated the protective effect of GGA against noxious agents in rat gastric mucosa and demonstrated that GGA dose-dependently increased COX-2 expression and prostaglandin E2 production (24). In the present study, the administration of GGA suppressed iNOS expression and dose-dependently attenuated DSS-induced colitis.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, we previously administered a COX-2 inhibitor to mice with DSS-induced colitis and demonstrated that the presence of a COX-2 inhibitor during colitis exacerbated the colitis and did not show a preventive effect against colitis-induced tumorigenesis (13). Nishida et al evaluated the protective effect of GGA against noxious agents in rat gastric mucosa and demonstrated that GGA dose-dependently increased COX-2 expression and prostaglandin E2 production (24). In the present study, the administration of GGA suppressed iNOS expression and dose-dependently attenuated DSS-induced colitis.…”
Section: Discussionsupporting
confidence: 68%
“…NF-κB is a family of dimeric transcription factors that control the expression of numerous genes involved in cell growth, regulation of apoptosis, and neoplastic transformation (20,21). It was discovered in 1986 as a nuclear factor that binds to the enhancer region of the κB chain of immunoglobulin in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hashimoto et al [40] have reported that GGA inhibits cancer invasion and progression by attenuating Rho activation and Ras-mitogen-activated protein kinase (MAPK) in the mevalonate pathway. Nishida et al [41] reported that GGA induces COX-2 expression and increases PGE 2 production via activation of the nuclear factor-kappa B (NF-jB) sites on COX-2 gene promoters. Yenari et al [39] and Wojcik et al [42] reported that the mechanism by which the anti-inflammatory effects are exerted by GGA is through the inhibition of NF-jB activation.…”
Section: Discussionmentioning
confidence: 99%